Cost-Utility Analysis of Anterior Cervical Discectomy and Fusion With Plating (ACDFP) Versus Posterior Cervical Foraminotomy (PCF) for Patients With Single-level Cervical Radiculopathy at 1-Year Follow-up. Issue 2 (March 2016) - Alvin, Matthew D.; Lubelski, Daniel; Abdullah, Kalil G.; Whitmore, Robert G.; Benzel, Edward C.; Mroz, Thomas E.
Abstract : Study Design: A retrospective 1-year cost-utility analysis. Objective: To determine the cost-effectiveness of anterior cervical discectomy and fusion with plating (ACDFP) in comparison with posterior cervical foraminotomy (PCF) for patients with single-level cervical radiculopathy. Summary of Background Data: Cervical radiculopathy due to cervical spondylosis is commonly treated by either PCF or ACDFP for patients who are refractory to nonsurgical treatment. Although some have suggested superior outcomes with ACDFP as compared with PCF, the former is also associated with greater costs. The present study analyzes the cost-effectiveness of ACDFP versus PCF for patients with single-level cervical radiculopathy. Methods: Forty-five patients who underwent ACDFP and 25 patients who underwent PCF for single-level cervical radiculopathy were analyzed. One-year postoperative health outcomes were assessed based on Visual Analogue Scale, Pain Disability Questionnaire, Patient Health Questionnaire, and EuroQOL-5 Dimensions questionnaires to analyze the comparative effectiveness of each procedure. Direct medical costs were estimated using Medicare national payment amounts and indirect costs were based on patient missed work days and patient income. Postoperative 1-year cost/utility ratios and the incremental cost-effectiveness ratio (ICER) were calculated to assess for cost-effectiveness using a threshold of $100, 000/QALY gained. Results: The 1-year cost-utility ratio for the PCF cohort was significantly lower ($79, 856/QALY gained) than that for the ACDFP cohort ($131, 951/QALY gained) ( P <0.01). In calculating the 1-year ICER, as the ACDFP cohort showed lower QALY gained than the PCF cohort, the ICER was negative and is not reported, meaning that ACDFP was dominated by PCF. Conclusions: Statistically significant and clinically relevant improvements (through minimum clinically important differences) were seen in both cohorts. Although both cohorts showed improved health outcomes, ACDFP was not cost-effective relative to the threshold of $100, 000/QALY gained at 1-year postoperatively, whereas PCF was. The durability of these results must be analyzed with long-term cost-utility analysis studies.